2021
DOI: 10.3389/fmicb.2021.711134
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Signatures of Paediatric Respiratory Disease: An Individual Participant Data Meta-Analysis

Abstract: Introduction: The airway microbiota has been linked to specific paediatric respiratory diseases, but studies are often small. It remains unclear whether particular bacteria are associated with a given disease, or if a more general, non-specific microbiota association with disease exists, as suggested for the gut. We investigated overarching patterns of bacterial association with acute and chronic paediatric respiratory disease in an individual participant data (IPD) meta-analysis of 16S rRNA gene sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Access to published data varies greatly among studies. For our meta-analysis [ 19 ], just over half of the 20 included studies had publicly available sequence data, and, at the time of the initial literature search, only two contained sufficient metadata to enable meaningful linking with the sequence data. There was also variability in terms of the types of samples that had been uploaded to public repositories: some publicly uploaded datasets included samples which were not explained or mentioned in the original article, potentially representing mock communities, sequencing controls, negative extraction controls, samples excluded from the original publication or samples from different studies that were uploaded under the same accession number.…”
Section: Data Accessibility Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to published data varies greatly among studies. For our meta-analysis [ 19 ], just over half of the 20 included studies had publicly available sequence data, and, at the time of the initial literature search, only two contained sufficient metadata to enable meaningful linking with the sequence data. There was also variability in terms of the types of samples that had been uploaded to public repositories: some publicly uploaded datasets included samples which were not explained or mentioned in the original article, potentially representing mock communities, sequencing controls, negative extraction controls, samples excluded from the original publication or samples from different studies that were uploaded under the same accession number.…”
Section: Data Accessibility Challengesmentioning
confidence: 99%
“…Our meta-analysis [ 19 ] identified two broad approaches to reporting antibiotic usage that are common among respiratory microbiota studies: either the time between a patient’s last antibiotic use and sampling is reported or, alternatively, no samples are taken from individuals with antibiotic exposure more recent than a specified cut-off date. The former can be challenging to accommodate in meta-analyses, as a standardised definition of “recent antibiotic use” is lacking.…”
Section: Accounting For Antibiotic Usage In Respiratory Microbiota St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the aforementioned approaches brings its own biases, including (but not limited to) differences in DNA extraction efficiency between different microbial cell types, PCR bias whereby the rRNA genes of some organisms are preferentially amplified over others (sometimes due to selection of PCR primers), and choice of database for assigning taxonomic identities to obtained sequence data (Pollock et al 2018). Differences in methodological approaches among different research labs can make it difficult to compare between studies, and there are increasing calls for standardisation of methods within the microbiome field (Costea et al 2017;Broderick et al 2021;Bodawatta et al 2022). While global initiatives such as the Earth Microbiome Project (Thompson et al 2017) speak to the power of methods standardisation, one must also acknowledge the challenges with attempting to develop a one-size-fits-all approach; indeed, in the authors' laboratory alone, several different DNA extraction protocols are used when working with different host animals.…”
Section: Sample Analysis -From Lab Bench To Computermentioning
confidence: 99%
“…Meta-analyses minimize this variation, providing a more precise estimation of microbiome effects. In this way, robust, generalizable microbiome-health relationships become identifiable (Broderick et al 2023). Moreover, meta-analyses unveil elusive trends and associations in combined data, facilitating links recognition between microbial groups or compositions and health conditions.…”
Section: Introductionmentioning
confidence: 99%